Unmasking the Network: The Power Dynamics Behind the Social Movement Against Election Postponement - Dewi, Evie Ariadne Shinta; Diyaulmuhana, Diyaulmuhana; Pratamawaty, Benazir Bona (Nyimak: Journal of Communication, 2024)
This study analyzes and visualizes the network dynamics of the "Tolak Penundaan Pemilu" movement on Twitter, focusing on network structure, types of relationships, and overall connectivity. Using Graph Theory to define the network and Resource Mobilization Theory (RMT) to understand the role of resources, particularly human resources, in mobilizing social movements, the study applies quantitative Social Network Analysis (SNA) to a dataset comprising 2,210 nodes and 1,406 edges. Data was collected through text mining using Netlytic and analyzed with Gephi and Ucinet. The results indicate that the network has a two-mode relationship type with a radial personal network communication pattern, and the relationship direction is directed and asymmetrical. The network structure consists of 35 components, 3 isolated nodes, 47 cutpoints, and no cliques, indicating a fragmented and hierarchical network nature. These findings provide insights into the distribution of information and support within the "Tolak Penundaan Pemilu" movement. This research contributes to the study of social network dynamics in political movements on Twitter by highlighting the interaction between network structure and resource mobilization, offering new perspectives on digital social movement organizational patterns, and enriching the understanding of how social networks influence and facilitate collective action in contemporary political contexts.Keywords: Social Movement, Graph Teory, Reject Election Postponement, SNA, Resource Mobilization TheoryAbstrakPenelitian ini menganalisis dan memvisualisasikan dinamika jaringan gerakan "Tolak Penundaan Pemilu" di Twitter, dengan fokus pada struktur jaringan, jenis hubungan, dan konektivitas keseluruhan. Menggunakan Teori Graf untuk mendefinisikan jaringan serta Teori Mobilisasi Sumber Daya (RMT) untuk memahami peran sumber daya, khususnya sumber daya manusia, dalam memobilisasi gerakan sosial, penelitian ini menerapkan analisis jejaring sosial (SNA) kuantitatif pada dataset yang terdiri dari 2.210 node dan 1.406 edge. Data dikumpulkan melalui text mining menggunakan Netlytic dan dianalisis dengan Gephi serta Ucinet. Hasil menunjukkan bahwa jaringan ini memiliki jenis hubungan dua mode dengan pola komunikasi jaringan personal radial, serta arah hubungan yang terarah dan asimetris. Struktur jaringan terdiri dari 35 komponen, 3 isolated node, 47 cutpoints, tanpa adanya clique, yang menggambarkan sifat jaringan terfragmentasi dan hierarkis. Temuan ini memberikan wawasan tentang distribusi informasi dan dukungan dalam gerakan "Tolak Penundaan Pemilu". Penelitian ini berkontribusi pada kajian dinamika jejaring sosial dalam gerakan politik di Twitter dengan menyoroti interaksi antara struktur jaringan dan mobilisasi sumber daya, memberikan perspektif baru tentang pola organisasi gerakan sosial digital, serta memperkaya pemahaman tentang pengaruh jejaring sosial dalam memfasilitasi aksi kolektif di konteks politik kontemporer.Kata Kunci: Gerakan Sosial, Graph Theory , Tolak Penundaan Pemilu, SNA, Resource Mobilization Theory